Variations in bacterial community during bioclogging in Managed Aquifer Recharge (MAR): A laboratory study. (February 2020) - Xia, Lu; Gao, Zongjun; Xu, Hailong; Feng, Guoping
Abstract: Understanding evolution of bacterial community diversity, composition, and structure is of great importance for targeted prophylaxis and treatment of bioclogging of reclaimed water after Managed Aquifer Recharge (MAR). Based on laboratory percolation experiments, temporal variations in bacterial 16S rRNA gene copy number and community diversity, composition, and structure were investigated using real-time quantitative polymerase chain reaction (qPCR) and high-throughput sequencing in this study. During the percolation experiments, the relative saturated hydraulic conductivity ( K s ') decreased from 1.0 to 0.011 at 588.3 h, indicating that a complete clogging occurred in the sand columns. Correspondingly, the bacterial 16S rRNA gene copy numbers reached a maximum of 3.9 × 10 9 copies per gram of sand at 180.5 h, and then decreased to 6.2 × 10 8 copies per gram of sand at the end of the test. Four microbial samples were collected in situ from the reclaimed water (SRW), and the clogged sand columns, namely SK0.52, SK0.08 and SK0.011, of which the K s ' values decreased to 0.52, 0.08 and 0.011, respectively. The Chao richness index values of the bacterial community were 352, 207, 205, and 197 for SRW, SK0.52, SK0.08, and SK0.011, respectively, revealing lower species richness in the sand columns. The Shannon index values were 3.27, 2.84, 3.51, and 3.21 for SRW, SK0.52, SK0.08, and SK0.011, respectively. Meanwhile, the Evenness index values were 0.56, 0.54, 0.67, and 0.61 for the four samples in turn. This result implied that the changes in bacterial diversity and evenness were not obvious. The principal coordinate analysis (PCoA) results showed major differences in bacterial community composition between the four samples. A variety of bacterial phyla were found, among which Proteobacteria were predominant. For the non-Proteobacterial phyla, Parcubacteria, Acidobacteria, Chlamydiae, Gracilibacteria, Chloroflexi, and Saccharibacteria disappeared when moving from the raw reclaimed water to the solid porous media. Instead, Bacteroidetes and Actinobacteria were detected in the sand samples. Although some differences existed, a core group of bacteria persisted and might play a critical role during MAR bioclogging. Highlights: Major clogging occurred during the simulated MAR involving surface infiltration. The characteristics of bacterial community varied based on laboratory percolation trials. The bacterial community richness decreased. No obvious change was observed in the bacterial community diversity or evenness. A core group of bacteria persisted and might have a significant effect on clogging.